CULTURAL ASPECTS REPRESENTATION IN ENGLISH TEXTBOOK AND ITS IMPLICATION ON ENGLISH LANGUAGE LEARNING - Ariawan, Soni (JOURNAL OF ADVANCED ENGLISH STUDIES, 2020)
Abstract. The present study investigates cultural aspects representation in an English textbook prescribed for senior high school in Indonesia which is officially published by Ministry of Education and Culture in 2017. The study aims to explore cultural aspects revealed in the textbook by employing Byram’s checklist of cultural dimensions and Cortazzi and Jin’s categories of culture as the theoretical frameworks. The data for analysis is selected from the textbook which includes conversations, reading texts and visual elements. The inclusion of national identity is pivotal for learners since the textbook is prescribed for senior high school students who are tremendously curious to determine their own characters. Regarding cultural aspects representation or categories, source culture or Indonesian culture is the most prominent with 61.2%, while target culture and international target culture achieve 19.8% and 14.9% respectively. The presence of source culture encompasses social interaction, school and family environment, national identity and national history as well as national geography. Where the target culture is concerned, the United States of America is the most highly represented inner circle country’s culture in the textbook, while India and Japan are the countries primarily represented in the international target culture category. The inclusion of source culture in the English textbook is fundamental since culture teaching can improve learners’ communicative competence; however, the representation of target culture and international target culture is also crucial to achieve linguistics as well as cultural competence. It is concluded that English textbook in Indonesia is on the way to its perfection in terms of proportionally represented cultural aspects. However, the presence of various cultural aspects of source culture, target culture and international target culture is also important to help students develop multicultural awareness and a certain level of respects as well as tolerance for others. in the use of student’s diary as well is presented as the implication of this research for further related studies.